Moving Towards Prosperity: Recent Reviews in the World of Economics - Nafdillah (Mustard Journal De Ecobusin, 2024)
This qualitative have a look at delves into the complicated dynamics of financial inequality thru a phenomenological lens, aiming to uncover the lived studies and perceptions of individuals from numerous socio-financial backgrounds. Using semi-structured interviews, a purposive sample of 20 members became engaged to explore their narratives concerning monetary mobility, perceptions of meritocracy, intersectional identities, and subjective understandings of wealth and poverty. The analysis found out a complicated interplay of things, highlighting the pervasive effect of socio-economic backgrounds on opportunities and effects, nuanced perspectives on meritocracy and fairness, the intersectionality of identities in shaping financial stories, and subjective interpretations of well-being past economic measures. By evaluating and contrasting those findings with present literature, this take a look at contributes to a deeper expertise of the multidimensional nature of financial inequality. The implications of those insights for coverage interventions and destiny studies instructions also are discussed.